STATUS OF CERTIFICATE ON THE BUILDING ON THE GREEN OPEN SPACE AREA (CASE STUDY OF CHANGING GREEN OPEN SPACE TO THE RIGHT OF BUILDING USE IN BANDAR LAMPUNG CITY) - Hariono, Hariono (Tadulako Law Review, 2019)
The author raised about the status of certificate of building rights in the area of green open space. will begin by revealing the green open space as one of the spatial arrangements in urban areas, will require the land as a container of green open space development in question. Development of green open spaces built in urban areas, related to the full utilization of land directly controlled by the state in the form of pertinent building rights. To ensure the legal certainty of the land for use of the building concerned, it is necessary to do so with the registration of the right to use the building. The permission granted by the municipal government to the conversion of green open space to the right to use the building is a form of abuse of authority by the city government of Lampung.